Formulasi Nugget Tempe dengan Penambahan Jamur Kuping dan Wortel terhadap Karakteristik Fisikokimia dan Sensoris - Fitriyani, Devi Nur; Rahayuni, Tri; Hartanti, Lucky (Agriculture Faculty, 2024)
Nuggets are a restructuring product of chicken meat, namely the product of small pieces of chicken meat which are then glued back together with food additives to become a product with a larger size. Nuggets are generally made from animal meat, so they are often called chicken nuggets. Chicken meat has a high fat and cholesterol content, so it is necessary to limit its consumption. There needs to be an alternative to replace meat nuggets into nuggets made from vegetable ingredients that contain protein, one of which is using tempeh and ear mushrooms and carrots to provide texture and increase fiber content. The purpose of this study was to obtain tempeh nugget formulations with the addition of mushroom and carrot for the best physicochemical and sensory characteristics. This study used a randomized block design (RBD) with one factor, namely the formulation of tempeh, ear fungus, and carrots (p) which consisted of 5 levels and 5 replications. The research data were processed using analysis of variance (ANOVA) with a level of 5% if the treatment had a significant effect then followed by the Honest Significant Difference (BNJ) test with a level of 5%. Sensory analysis using the Friedman test. Determination of the best treatment was tested using the effectiveness index test. The results showed that the tempeh nugget formulation with the addition of ear mushrooms and carrots which produced the best physicochemical and sensory properties was 70% tempeh formulation, 15% ear mushroom, and 15% carrot.